1990
DOI: 10.1111/j.1439-0450.1990.tb01072.x
|View full text |Cite
|
Sign up to set email alerts
|

Erosive Colitis in Experimental Canine Leishmaniasis

Abstract: Summary Six 4 month‐old beagles were inoculated with Leishmania infantum, three of them intraperitoneally (Group A) and the other three intravenously (Group B). The animals from Group A were killed at 109, 433 and 592 days after inoculation and animals from Group B 109, 171 and 334 days after inoculation. At 350 days (Group A) and 275 days (Group B) after inoculation, dogs started to develop a chronic large bowel diarrhoea. At necropsy a diffuse colonic and rectal wall thickening of gradually increasing severi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
22
0
1

Year Published

1996
1996
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 7 publications
4
22
0
1
Order By: Relevance
“…We observed parasites associated with the inflammatory response throughout the mucosa, but without inducing severe pathologies, such as ulcers or necrosis. The immunohistochemical morphometric analysis revealed higher parasite loads in the colon than in the jejunum, as previ-ously reported by our group (25) and in accordance with other reports (31)(32)(33)(34)(35)(36).…”
Section: Discussionsupporting
confidence: 80%
“…We observed parasites associated with the inflammatory response throughout the mucosa, but without inducing severe pathologies, such as ulcers or necrosis. The immunohistochemical morphometric analysis revealed higher parasite loads in the colon than in the jejunum, as previ-ously reported by our group (25) and in accordance with other reports (31)(32)(33)(34)(35)(36).…”
Section: Discussionsupporting
confidence: 80%
“…In the previous works, the presence of amastigotes of L. infantum has been described in gastrointestinal tissues of dogs infected with CVL, particularly in the mucosa of cecum and colon where the parasites were detected in higher burden (KEENAN et al, 1984 a, b;GONZÁLEZ et al, 1990;ADAMAMA-MORAITOU et al, 2007;PINTO et al, 2011;FIGUEIREDO et al, 2013). In the present work, macrophages containing L. infantum amastigotes were also found in the large (colon) and in the small intestines (duodenum, jejunum and ileum) with a mononuclear inflammatory infiltration, represented mainly by macrophages, lymphocytes and plasma cells in the majority of the cases of infected dogs from G1 group.…”
Section: Discussionmentioning
confidence: 96%
“…In cases of experimental infection, González et al (1990) observed a severe chronic inflammatory process in the mucosa and submucosa of the colon and rectum of dogs. As a result, focal micro-erosions developed in the mucosal surface, thereby reducing the area of the large bowel available for water absorption and causing diarrhea.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations